PENGARUH MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN MINITAB PADA POKOK BAHASAN STATISTIKA - Sulaiman, Sulaiman; Khoiriyah, Siti; Nihayati, Nihayati (JURNAL e-DuMath, 2018)
One of the external factors that influence student learning is the media that support learning activities. The media interactive learning are to support methematical learning activities on statistical subjects, including minitab. Thefore, this study aims to see whether the use of minitab has a significant influence on student learning outcomes. The population in this study were student of class XI SMAN 1 Adiluwih consisting of two classes of science and two classes of social studies. The sample was taken throught the cluster random technique, so that two classes of science were chosen as the research it. Based on the results of data analysis,it was found that there were differences in the mean outcomes of students who use minitab. The difference is known through a hypothesis test wich states that t test = 12.67 are in the critical area which causes H0 to be rejected. This means that the application of learning using Minitab has a different effect. This difference is seen in terms of the average learning outcomes which are the output of the learning process. Further analyzed, it turns out that the mean learning outcomes of students who use the Minitab program is better than those who do not use Minitab. This is seen from the results of the test which states that Ztest= 3.41 are in the critical area which causes H0 to be rejected so that it can be concluded that the implementation of the Minitab program is best.Keyword : Minitab, Achievement.